Effects of Insect Density, Movement Period, and Temperature on Three-Dimensional Movement and Distribution of Adult Cryptolestes ferrugineus (Coleoptera: Laemophloeidae). Issue 3 (5th May 2022) - Bharathi, Vimala S K; Jayas, Digvir S; Jian, Fuji
Abstract: Knowledge on three-dimensional (3D) movement and distribution of Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae) in grain bulks assists in the prediction of their distribution inside a bin. The following experiments were conducted to determine the 3D dispersal patterns of adult C. ferrugineus in wheat with 14.5% moisture content: 1) at various insect densities (0.35, 1.77 and 3.53 A/kg (adults/kg) at 20°C and in 24 h movement period; 2) in different movement periods (6, 24, and 72 h) at 20°C and 0.35 A/kg insect density; and 3) at different temperatures (20, 30 and 35°C) at 0.35 A/kg density in 24 h movement period. To create the densities of 0.35, 1.77, and 3.53 A/kg, 100, 500, and 1, 000 adults were introduced in about 285 kg wheat, respectively. The 285 kg of wheat was kept in 343 mesh cubes, which in turn were packed in a wooden box. The introduced adults were counted at the end of the movement periods. Adult C. ferrugineus tended to move downward from the point of introduction, and then diffused throughout the grain bulk. The effects of insect densities, movement periods, and temperatures on the dispersion pattern of insects were similar in 1D columns, 2D chambers, and 3D grain bulk.